Strategi Pengembangan Kawasan Pariwisata DAM Trinsing Berdasarkan Kompenen 6A - Manihuruk, Jonathan; Nugroho, Rizky Arif; Hidayat, Arief; Pratama, Maryo Inri (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Tourism is one of the sustainable sectors in North Barito Regency whose existence is important for regional sustainability. One of the mainstay tourist attractions is the Trinsing Dam which is located in Trinsing Village, South Teweh District. However, there needs to be systematic and objective development so that Trinsing Dam tourism can continue in a sustainable manner. The development of Trinsing Dam tourism is supported by local government policies such as the North Barito Regency RTRW 2019 - 2039 and North Barito Regency RIPPDA 2019 - 2025. One step that can be taken is development based on the 6A tourism components, namely Attraction, Amenities, Ancillary, Accommodation, Accessibilities and Activities. Development begins by collecting data in the form of a general description of tourism and existing conditions collected from government documents, interviews and observations. These data are used as material for analysis and evaluation of Trinsing Dam tourism conditions. After that, the Trinsing Dam tourism development strategy was formulated using the SOAR (Strength, Opportunities, Aspirations and Results) method. Then a development strategy is obtained, namely maintaining and developing tourism variables that are already good or ideal as a basisfor developing other variables such as collaboration and cooperation between the community and its culture and tourist attractions, improving cleanliness systems, repairing damaged road points, improving facilities, improving service systems and additional accommodation infrastructure.